2022
DOI: 10.1007/s12144-022-02754-3
|View full text |Cite
|
Sign up to set email alerts
|

Nighttime lights, urban features, household poverty, depression, and obesity

Abstract: Nighttime Light Emission (NLE) is associated with diminished mental and physical health. The present study examines how NLE and associated urban features (e.g., air pollution, low green space) impact mental and physical wellbeing. We included 200,393 UK Biobank Cohort participants with complete data. The study was carried out in two steps. In Step1, we assessed the relationship between NLE, deprivation, pollution, green space, household poverty and mental and physical symptoms. In Step2, we examined the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Similarly, in the Netherlands, NTL exposure within 100 meters of residence was related to higher depressive symptoms among individuals aged 18 to 65, even after adjusting for confounding factors like air pollution with no such relationship observed for larger 600-meter buffers around residences [81]. This was confirmed by Liao et al (2022) [3] using data extracted from United Kingdom Biobank Cohort participants to associate higher NTL with increased mental, including depressed mood, tiredness/lethargy, and physical health problems such as obesity as well as more air pollution, less green space, higher economic and neighborhood deprivation and higher household poverty. Leveraging this dataset, a further study established a connection between heightened NTL exposure and an elevated risk of substance use disorder and depression, particularly in individuals with increased iron deposition in the hippocampus and basal ganglia [48].…”
Section: A Decade Of Remotely Sensed Epidemiology: Academic Literatur...mentioning
confidence: 74%
See 2 more Smart Citations
“…Similarly, in the Netherlands, NTL exposure within 100 meters of residence was related to higher depressive symptoms among individuals aged 18 to 65, even after adjusting for confounding factors like air pollution with no such relationship observed for larger 600-meter buffers around residences [81]. This was confirmed by Liao et al (2022) [3] using data extracted from United Kingdom Biobank Cohort participants to associate higher NTL with increased mental, including depressed mood, tiredness/lethargy, and physical health problems such as obesity as well as more air pollution, less green space, higher economic and neighborhood deprivation and higher household poverty. Leveraging this dataset, a further study established a connection between heightened NTL exposure and an elevated risk of substance use disorder and depression, particularly in individuals with increased iron deposition in the hippocampus and basal ganglia [48].…”
Section: A Decade Of Remotely Sensed Epidemiology: Academic Literatur...mentioning
confidence: 74%
“…The assumption is that NTL emission, indicative of developed land, can infer the urban extent, economic activity across scales, and light exposure impacts on health [41,42]. DMSP/OLS NTL data has been associated with adverse mental health outcomes, including a higher risk of autism spectrum disorders [43], and increased depressive mood [3]. While a direct link to mental health may not be evident, nighttime light can serve as an important proxy for studying the potential relationships between urbanization, lower socioeconomic status [3], and factors such as disrupted sleep patterns [44] influencing mental health outcomes.…”
Section: Dmsp-ols and Viirsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ACA and its provisions have the remarkable potential to provide individuals with obesity the care they need prior to developing downstream complications such as diabetes, cardiovascular disease, and certain cancers. Although our study findings do not directly assess policies aimed at narrowing or eliminating racial/ethnic disparities in upstream obesity‐related factors, we believe that addressing healthy food availability [42, 43], neighborhood green space [44], and food security [45] is needed to improve health equity among racial/ethnic minorities at risk for or affected by obesity.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a review on intervention trials to improve sleep conducted to quantify the effect of sleep on mental health, revealed that depression symptoms were improved by optimizing sleep with moderate effect size ( g = −0.63), (Scott et al, 2021). Night‐time light pollution constitutes a serious hazard to good sleep, and has been shown among other environmental variables to characterize urban areas in which depression, obesity, or household poverty prevail to a stronger extent compared to regions with lower light pollution (Liao et al, 2022). Concerning daylight entering the home, analyzing data from the LARES study revealed that insufficient natural light exposure at one's home was related to 1.4 times higher odds for doctor‐diagnosed depression (Brown & Jacobs, 2011).…”
Section: Introductionmentioning
confidence: 99%